Music Therapy Interventions for Stress Reduction in Adults With Mild Intellectual Disabilities: Perspectives From Clinical Practice - de Witte, Martina; Lindelauf, Esther; Moonen, Xavier; Stams, Geert-Jan; van Hooren, Susan (Frontiers in Psychology, 2020)
Stress is increasingly being recognized as one of the main factors that is negatively affecting our health, and therefore there is a need to regulate daily stress and prevent long-term stress. This need seems particularly important for adults with mild intellectual disabilities (MID) who show to have more difficulties coping with stress than adults without intellectual disabilities. Hence, the development of music therapy interventions for stress reduction, particularly with populations where needs may be greater, is becoming increasingly important. In order to gain more insight into the practice-based knowledge on how music therapists lower stress levels of their patients with MID during music therapy sessions, we conducted focus group discussions with music therapists working with adults with MID (N = 13) from different countries and clinical institutions. Results provide an overview of the most used interventions for stress reduction within and outside of the music. Data-analysis resulted in the further specification of therapeutic goals, intervention techniques, the use of musical instruments, and related therapeutic change factors. The main findings indicate that music therapists used little to no receptive (e.g. music listening) interventions for stress reduction, but preferred to use active interventions, which were mainly based on musical improvisation. Results show that three therapy goals for stress relief could be distinguished. The goal of “synchronizing” can be seen as a sub goal because it often precedes working on the other two goals of “tension release” or “direct relaxation,” which can also be seen as two ways of reaching stress reduction in adults with MID through music therapy interventions. Furthermore, the tempo and the dynamics of the music are considered as the most important musical components to reduce stress in adults with MID. Practical implications for stress-reducing music therapy interventions for adults with MID are discussed as well as recommendations for future research. Keywords: music therapy, stress, stress release, relaxation, improvisation, change factors, mechanism of change